2017
DOI: 10.4017/gt.2017.16.3.008.00
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effectiveness of ActivLife training in people over 60 years of age: A pilot study

Abstract: Background One of the most important geriatric problems which increases the risk of injury and disability is falling. The consequences involve fractures of the hips and femoral neck, leading to restrictions in mobility, independence and the quality of life. Reduction of the risk is the main challenge of modern geriatrics. Aim The aim of the study was to analyze the effectiveness of training using the ActivLife system in women over 60 years of age who have declared difficulties in maintaining the balance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The device is also equipped with a mechanism assisting the patient in standing up. Performing squats with the equipment has been shown to increase muscle strength on the lower parts of the body (Les et al 2017). The screen has a Kinect sensor that allows the software to determine if the patient is doing the exercise correctly.…”
Section: Methodsmentioning
confidence: 99%
“…The device is also equipped with a mechanism assisting the patient in standing up. Performing squats with the equipment has been shown to increase muscle strength on the lower parts of the body (Les et al 2017). The screen has a Kinect sensor that allows the software to determine if the patient is doing the exercise correctly.…”
Section: Methodsmentioning
confidence: 99%
“…Evans (1999) found that the use of simple forms of movement in such a way to associate physical activities with pleasure, relaxation, and fun is most effective in stimulating physical activities among seniors. Specialized intervention programs are needed to properly stimulate physical activities related to fall prevention, such as muscle strength or dynamic balance, as well as cognitive factors (Leś et al 2017). Therefore, many interventions have been developed to stimulating physical exercises and reducing the fear of falling (Gillespie et al 2012;Patel et al 2012;Sherrington et al 2008;World Health Organisation 2007;Zijlstra et al 2005).…”
Section: Introductionmentioning
confidence: 99%